Perlindungan Tenaga Kerja Tanpa Kontrak Kerja Pada Kapal Penangkap Ikan (Bobo) - Nila Juwita Mahulette; Sarah Selfina Kuahaty; Sabri Fataruba (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: Protection of Workers who work without an employment contract on fishing vessels owned by CV Tehoru. In carrying out work between workers and employers, there must always be a contract or work agreement.Purposes of the Research: Analyzing and Reviewing how to pay responsibilities to fishing workers by CV Tehoru as the employer.Methods of the Research: This research is included in normative legal research, namely research examining positive legal provisions, legal principles. Legal principles and doctrines to answer legal issues faced.Results of the Research: CV Tehoru uses a time unit wage system and a unit wage system. The time unit wage can be given by the employer based on the working time, that is, a matter of hours, days or a month, while the unit wage can be given based on the income result in accordance with the work agreement between the two parties. Although wages are based on units of result and units of time, a company must also adhere to a legal system that regulates drinking wages which are regulated by the central government or local governments.